De Sodoma: la historia por contar. Sobre literatura de tema homosexual en Cuba - Cabrera, Yoandy (CUADERNOS KÓRE, 2011)
Analysis of the Pedro Pérez Rivero’s essays book De Sodoma vino un angel, which tries to be a synthetic study about the homosexual subject in the Cuban literature. We present some examples and criticism of the procedures that we consider wrong in the construction of the author’s speech. We analyze the concepts and differences between homoerotism and homosexuality. We conclude with a proposal for a more serious study and with more coherence about this subject.